2021
DOI: 10.1021/acsomega.0c05544
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Evaluation Model of the Nutritional Quality of Edible Vegetable Oil Based on Dietary Nutrient Reference Intake

Abstract: Edible vegetable oils can provide most of the fatty acids, vitamin E, and certain phytochemicals necessary in the daily human diet to facilitate the required physiological activities. However, there are many types of edible vegetable oils on the market, and evaluating their nutritional quality is a matter of significant interest to consumers and producers. Most of the existing research studies that comparatively analyze and qualitatively describe the type, content, and proportion of nutrients in edible vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Young acknowledges the positive effects of essential fatty acids, but in a rather "interesting" way, lacking evidence: "they lubricate the surface of joints", "they insulate the body" (Young and Young, 2006). These dietary suggestions are not fundamentally wrong, as they closely meet the official dietary recommendations regarding their fatty acid compositions, but because of the restrictions, the fatty acid content of the alkaline diet can be a crucial question (Szűcs, 2016;Zhao et al, 2021).…”
Section: Oilseeds Vegetable Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young acknowledges the positive effects of essential fatty acids, but in a rather "interesting" way, lacking evidence: "they lubricate the surface of joints", "they insulate the body" (Young and Young, 2006). These dietary suggestions are not fundamentally wrong, as they closely meet the official dietary recommendations regarding their fatty acid compositions, but because of the restrictions, the fatty acid content of the alkaline diet can be a crucial question (Szűcs, 2016;Zhao et al, 2021).…”
Section: Oilseeds Vegetable Oilsmentioning
confidence: 99%
“…contamination of oils) In a healthy diet, the oilseed and the usage of vegetable oils are recommended in normal amounts. (Szűcs, 2016;Zhao et al, 2021) efficacy and the prophylactic features of the alkaline diet; thus, it can be stated that an alkaline diet does not support the maintenance of our health, but can rather be harmful due to its rather strict, selective, and restrictive nature. When following this diet, the lack of sufficient calcium and protein intake would increase the risk of several deficiencies.…”
Section: Milk and Dairy Productsmentioning
confidence: 99%
“…Table 1. Nutritional and physiochemical profile of selected oils (coconut oil, flaxseed oil, olive oil, sunflower oil) (a: [21]; b: [30]; c: [31]; d: [32]; e: [24]; f: [20]; g: [33]; h: [34]; i: [35]; j: [36]; k: [37]; l: [38]; m: [39]; n: [40]; o: [41]). An 8 week clinical trial of VOs supplementation on anthropometric and biochemical parameters in 75 obese women revealed that the CO group resulted in more weight loss and lowered BMI, percent body fat, waist circumference, and waist-to-height ratio in the anthropometric examination.…”
Section: Selection and Collection Of Datamentioning
confidence: 99%
“…(2). Benefits of vegetable oils are associated with fatty acids composing them: saturated (C6:0-C20:0, no double bonds) monounsaturated (C16:1-C20:1, one double bond) and polyunsaturated (C18:2-C24:6), two up to six double bonds) (2, 3), essential components: macroand microelements, vitamins A, C, K, and E (tocopherols, tocotrienols), phytosterols, phytostanols, carotenoids, chlorophylls, polyphenols, flavonoids, acting as antioxidants and health promoting (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%